Characterization of B-box family genes and their expression profiles under abiotic stresses in the Melilotus albus - Nian, Lili; Zhang, Xiaoning; Liu, Xingyu; Li, Xiaodan; Liu, Xuelu; Yang, Yingbo; Haider, Fasih Ullah; Zhu, Xiaolin; Ma, Biao; Mao, Zixuan; Xue, Zongyang (Frontiers in Plant Science, 2022)
B-box (BBX) proteins are one of the zinc-finger transcription factor that plays a critical role in plant development, growth, and multiple stress responses. Although BBX genes have been reported in many model organisms, no comprehensive study has yet been conducted on the BBX genes in Melilotus albus, and the biological functions of this family remain unknown. In this study, a total of 20 BBX (MaBBX) genes were identified in M. albus and were phylogenetically divided into five clades. BBX members within the same clade showed similar conserved domain, suggesting similarity of potential biological function. Analysis of MaBBX conserved motifs showed that every subfamily contained two common motifs. Distribution mapping shows that BBX proteins are nonrandomly localized in eight chromosomes. The synteny showed that most homologous gene pairs of the MaBBX gene family were amplified by segmental replication, which meant segmental replication was the main way for the MaBBX gene family to evolve. Additionally, the cis-element analysis predicted light-responsive, various hormone and stress-related elements in the promoter regions of MaBBXs. Furthermore, the expression levels of all 20 MaBBX genes were detected by qRT-PCR under salt, cold, and dark stresses in M. albus. Moreover, it was observed that 16 genes had higher expression levels after 3 h of salt treatment, 10 genes were significantly upregulated after 3 h of cold treatment, and all genes were up regulated after 3 h of dark treatment, and then appeared to decline. In addition, it was also noticed that MaBBX13 may be an important candidate for improving tolerance to abiotic stress. The prediction of protein tertiary structure showed that the tertiary structures of members of the same subfamily of MaBBX proteins were highly similar. The hypothesis exhibited that most of the MaBBX proteins were predicted to be localized to the nucleus and cytoplasm and was validated by transient expression assays of MaBBX15 in tobacco leaf epidermal cells. This study provides useful information for further investigating and researching the regulatory mechanisms of BBX family genes in response to abiotic stresses in M. albus.